Solution-processed n-type Bi2Te3 − xSex nanocomposites with enhanced thermoelectric performance via liquid-phase sintering - Zhang, Chaohua (2020)
The much slower progress in enhancing the thermoelectric performance of n-type Bi2Te3 than that of p-type Bi2Te3 based materials in the past decade hinders the widespread use in power generation and refrigeration. Here, a facile bottom-up solution-synthesis with spark plasma sintering (SPS) process has been developed to build n-type Bi2Te3−xSex bulk nanocomposites, which substantially improves the power factor and decreases the lattice thermal conductivity by tuning the interface scattering of phonons and electrons. The stoichiometric composition in ternary Bi2Te3−xSex nanocomposites is also tuned to optimize the carrier concentration and lattice thermal conductivity. The optimized bulk nanocomposite Bi2Te2.7Se0.3 exhibits a ZT of 1.1 at ~371 K, which is comparable to the corresponding commercially available ingots. Our results demonstrate the great potential of the solution-processed n-type Bi2Te3−xSex nanocomposites for cost-effective thermoelectric applications.